2016
DOI: 10.1212/wnl.0000000000002632
|View full text |Cite
|
Sign up to set email alerts
|

Ventral tegmental area deep brain stimulation for refractory chronic cluster headache

Abstract: This study provides Class IV evidence that VTA-DBS decreases headache frequency, severity, and headache load in patients with medically intractable chronic cluster headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 35 publications
2
102
0
Order By: Relevance
“…We note that some of these studies were performed on medically refractory CH patients . In the study by Ertsey and colleagues, ECH patients had lower, that is, poorer, scores in all the SF‐36 domains compared to controls and migraine patients, with a significant difference for SF‐36 domains evaluating bodily pain and social functioning.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We note that some of these studies were performed on medically refractory CH patients . In the study by Ertsey and colleagues, ECH patients had lower, that is, poorer, scores in all the SF‐36 domains compared to controls and migraine patients, with a significant difference for SF‐36 domains evaluating bodily pain and social functioning.…”
Section: Resultsmentioning
confidence: 95%
“…Seven studies have tested QoL in CH using the Medical Outcome Study Short Form, 36 and 12‐item version (SF‐36 and SF‐12) . The SF‐36 comprises 8 scales that can be summed up into 2 composite scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 2 months of crossover blind study they did not find significant differences between the 2 groups, but in the later open phase (10 months) 6 out of 11 patients had more than 50% improvement, including 3 patients who became pain free [22]. Akram et al [23] reported 60% improvement in headache frequency and 30% improvement in headache severity in an open label series of 21 patients. In our series, all of the patients improved in terms of the number and duration of pain attacks.…”
Section: Discussionmentioning
confidence: 94%
“…Fontaine et al [10] believe that the active contacts are located in a bridging zone between the hypothalamus and the mesencephalic gray matter, and Clelland et al [11] believe that they are located in the gray matter of the mesencephalic tegmentum. Akram et al [23] also place their target at the mesencephalic tegmentum, just anterior to the nucleus ruber. Most of the authors agree that the trigeminal autonomic reflex (TAR) plays an important role in the pathophysiology of CH [26].…”
Section: Discussionmentioning
confidence: 99%